Zastosowanie sztucznych sieci neuronowych w językoznawstwie - Obrębska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
Artificial Neural Networks (ANN) are software systems inspired by biological models of the brain. They are capable of learning patterns and relations from input data. The ability to generalise knowledge enabling them to deal with previously unseen input data, so they can solve problems, that other software can’t. This paper presents a simple artificial neural network which classifies sentences into three classes: akceptable sentences, unakceptable sentences and trivial sentences. The main goal of this work is to show, how useful in linguistic Artificial Neural Networks could be.